PENGARUH GAYA KEPEMIMPINAN GENERAL MANAGER TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN DI HOTEL GRAND INNA KUTA - Utari, Dewa Ayu Kade Yani; Dewi, LGLK.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p20, 2023)
The success or failure of a hotel company is inseparable from the role of Human Resources (HR). The importance of the role of human resources cannot be separated from a leader in carrying out activities as well as job satisfaction and performance from employees. A leader has different type of leadership style on leading his subordinates. Whether or not the leadership style is able to influence the job satisfication and perfomance of his subordinates. This research was conducted to determine the effect of leadership style on job satisfaction and employee performance at the Grand Inna Kuta Hotel. The sampling technique used census sampling technique by distributing 159 questionnaires to employees of the Grand Inna Kuta hotel. The data used was a likert scale model questionnaire which was calibrated using validity and reliability tests. The data analysis technique uses the partial least square technique – structural equation modeling (PLS-SEM). Based on processing with smartPLS software, the results show that there is a significant positive influence between leadership style on job satisfaction, there is a significant positive effect between leadership style on employee performance, and there is a significant positive effect between job satisfaction on employee performance.